The differential diagnoses and complications of scabies variants - Jacob Al-Dabbagh; Razan Younis; Rasha Sliman (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Scabies is a common infection that affects people all over the world and has various presentations and impacts depending on the clinical situation. It is caused by the mite Sarcoptes scabiei var. hominis, an obligate ectoparasite that resides in the epidermis of the human skin. In this article, we present a review of the differential diagnoses and complications of scabies and scabies variants. We also present a summary of the etiology and the current diagnostic methods of scabies.